Legal protection for sexually abused young males by adult women in Malaysia / Intan Rafeah Abdul Rahim, Khairunnisah Laliman and Hasifulkhair Mohd Jamaluddin - Abdul Rahim, Intan Rafeah; Laliman, Khairunnisah; Mohd Jamaluddin, Hasifulkhair (2007)
This dissertation examines the law or lack of it in Malaysia with regard to the legal protection offered to sexually abused young males by adult women. This is done by looking through the Penal Code which is the authority for all criminal offences including but not limited to sexual offences and also by comparing legislations concerning sexual offences in the United Kingdom to form a guideline to unmask the loopholes in the Malaysian legislation. Protection for young males against being sexually abused by adult females are not provided for and the reasons as to why this is so. Hence, this will lead to the discussion with regards to society's views and perception of the situation and how this has hampered the development of the law in helping to protect young males from being sexually abused by females. Therefore, a recommendation is proposed to enact either a new legislation or to rectify the existing loopholes and to offer protection to the young males in cases where they are subjected to any sexual abuse by adult females.